Capitalization and bank performance: Evidence from Nigerian Banking Sector - Adewale Muritala Taiwo; Muftau Adeniyi Ijaiya; Ahmed Oluwatobi Adekunle; Mobolaji Kafayat Abidoye (e-Finanse: Financial Internet Quarterly, 2017)
The study examines the impact of capitalization on bank performance of some selected commercial banks in Nigeria using econometric analysis on annual time series data of ten banks over the period of 2006 to 2014. The results from a Levin, Lin & Chu unit root test show that all the variables were non-stationary. The results from a Panel Least Square (PLS) estimate found that operating expenses, bank size and bank loan are negatively related to profitability but only bank loans are significant. On the other hand, bank deposit and bank liquidity are positively related to profitability but not significant. This conclusion has important policy implications for emerging countries like Nigeria as it suggests that capitalisation and total assets of a bank should be periodically evaluated. The regulatory authorities will therefore need to put in place appropriate machinery that will address issues of bank liquidity and assure asset quality in the industry.
Keywords: G21; L25; O55; 330; Capitalization; Bank Performance; Commercial Bank; Nigeria